EVALUASI DAN USULAN PERBAIKAN KESEIMBANGAN LINTASAN PRODUKSI UNTUK MENCAPAI TARGET PRODUKSI DENGAN PENDEKATAN SIMULASI PADA WORKSHOP 3 DI PT. FACO GLOBAL ENGINEERING - Reza Primadhana; Parwadi Moengin; Sucipto Adisuwiryo (JURNAL TEKNIK INDUSTRI, 2013)
PT. FACO Global Engineering is a national company that manufactures Transformer Tank.The problems that arise on the production floor in Workshop 3 is a common difficulty in achievingproduction targets precisely at the appointed time this problem may be related to its unbalancedproduction line .. Average yield Transformer Tank produced today is 1 unit per week, while theproduction target set is 2 units per week.The methodology used is to use the simulation. The data obtained was then calculated andanalyzed the workload of each station. Utility work station is currently the largest existing utilities inthe workstation and welding with a cutting wheel percentages respectively 91.65% and 76.45%. Forutility work station is the smallest percentage of work stations fullfitting with 3.76%. This can beovercome by the proposed model are given 6. Model 2 the best proposal is the transfer station operatorto work painting and cutting wheel 1 fullfitting operator work station to drilling.